Culture, Kinesiology, and the Free Society. Issue 2 (3rd April 2018) - Twietmeyer, Gregg
ABSTRACT: In Notes Towards the Definition of Culture, T.S. Eliot asked whether culture should be understood as "essentially, the incarnation (so to speak) of the religion of a people." By "incarnation, " Eliot meant that "what we believe is not merely what we formulate and subscribe to, but that behavior is also belief ." It is, Eliot insisted, our actions, and not merely our ideas, which matter. Together, our actions and our ideas embody and then give life to culture. "Religion" is, no doubt, a contested term. For present purposes, all that needs to be conceded to make Eliot's point worth pursuing is that every culture has some conception of the good, the true, and the beautiful, which it promotes, encourages, and thereby cultivates . What implications does this have for kinesiology? I will examine three points. First, the discipline of kinesiology cannot be abstracted from the culture in which it finds itself, without becoming an anti-culture. This fact means that kinesiology must necessarily attend to the ways in which physical activity is embedded in the historical, anthropological, sociological, and philosophical foundations of society. Second, kinesiology contributes to the cultivation or brutalization of society. This results from the attention paid (or not paid) to the question of truth in the field. Such attention to truth requires recognition of the epistemological limits of science as well as to the importance of free-will, choice, and example. Finally, kinesiologists must be willing to cultivate and defend intellectual freedom as part of a free society. A free society allows for a diversity of opinions, not as end in itself, but as the vehicle by which fallible human beings approach the truth.